Analysis of the Environmental Benefits of Organic Agriculture: Exploring the Environmental Advantages of Organic Agriculture (Journal of Advances and Scholarly Researches in Allied Education, 2021)
By the end of the 1980s and especially in the 1990s, organic agriculture came to the forefront in response to the growing awareness of environmental conservation issues. Organic agriculture is a traditional, viable, low input use and sustainable method of agriculture to produce healthy food. It helps to reduce environmental and can strengthen the natural resource base. It ensures sustainable farm production. It is one of the fastest growing sectors of Agricultural production and plays an important role as an alternative and safe food production process. This system ensures the production of high quality food while conserving the soil fertility and enhancing its fertility. It includes all Agricultural system which promotes production practices that are environmentally, socially and economically sound. It consider the local soil health as a key to the successful production. It aims to optimize quality in all aspects of agriculture and the environment. Thus, it helps in a attaining an eco- friendly and sustainable production. This paper focuses on the environmental benefits and constraints of organic agriculture.